HUBUNGAN PENGETAHUAN DENGAN TINGKAT KESIAPSIAGAAN MENGHADAPI BENCANA TANAH LONGSOR PADA SISWA SEKOLAH DASAR DI DESA NGAGRONG KECAMATAN GLADAGSARI KABUPATEN BOYOLALI - Titik Anggraeni; Andilouis Kristiawan; Vina Asna Afifah; Herbasuki Herbasuki (Jurnal Cakrawala Keperawatan, 2024)
Background: Boyolali Regency is one of the areas prone to landslides because it contains Mount Merapi and has a steep topography. Many villages are located at the foot of Mount Merapi and Merbabu, one of which is Ngagrong village. Ngagrong Village and SD N 2 Ngagrong are one of the villages supported by PMI Boyolali Regency. Because they are located in areas prone to landslides, researchers want to know the knowledge and level of preparedness, especially elementary school students. Objectives: To determine the relationship between knowledge and the level of preparedness for landslides among elementary school students in Ngagrong village, Gladagsari subdistrict, Boyolali district. Method: This research design uses descriptive correlational with a cross sectional approach. The data collection technique was carried out using a questionnaire. The population in this study was 97 students at SD N 2 Ngagrong. The sample in this research was 51 students in grades 4, 5, 6. The data was processed using the SPSS program for univariate analysis with frequency distribution and bivariate with the Spearman's rho correlation test. Result: The research results show (1) The level of students' knowledge of disasters is in the good category as many as 51 people (100%). 2) The level of student preparedness for landslides is included in the very prepared category as many as 51 people (100%). 3) There is a significant relationship between knowledge and the level of preparedness for landslides among elementary school students in Ngagrong village, Gladagsari subdistrict, Boyolali district with a significance result of 0.02 (p<0.05). The strength of the correlation between the two variables is included in the sufficient category with a coefficient value correlation of 0.416. Conclusion: There is a relationship between knowledge and the level of preparedness for landslides among elementary school students in Ngagrong village, Gladagsari subdistrict, Boyolali district.